Understanding the Theory of Special Relativity - Oh, Jun-Young (Understanding the Theory of Special Relativity, 2021)
The process of the coherence between component theories in a conceptual frame increasing through assumptions or premises functioning as axioms to derive new theoretical theses is a characteristic of the formation process of Einstein’s theory of special relativity. First section, the purpose of this book is to make a proposal regarding appropriate education of the special theory of relativity through this process of increasing overall coherence. It is a cyclical and ecological learning method and not a linear and mechanical learning method. Preliminarily, to understand the characteristics of Einstein’s special theory of relativity which has coherence between all the theories, and ultimately, to make a proposal on the education of the special theory of relatively through increases in coherence. Second section, the book is to understand The theory of Special Relativity based on Einstein's Logical procedures for Science Education as a first step, adheres to Galileo's opinion that Einstein's first axiom does not exist in any way to test absolute motion in any way. and the second axiom follows Maxwell's equations and experimental facts that say that light is always moving at a constant speed in a vacuum no matter how the sender (source of light) or the receiver moves. The Newton’s metaphysics of the absoluteness of time and space has collapsed, while the principle of the absoluteness and finite of the speed of light has been connected with Einstein’s time-space.